Loan Loss Provisions Determinants: Evidence in Chinese Banks - HU, RUI (2011)
Loan loss provision is an important concept in banking. That is, it helps banks to prevent credit risk, manage regulatory capital, smooth income and maintain financial system stability. This paper seeks to examine loan loss provision determinants in Chinese banks using 110 bank-year observations over the period of 2001-2010. Ratio analysis, Random Effects model and the Generalized Method of Moments (GMM) Estimator method are used to assist our analysis. The finding suggests that Chinese banks on average follow an income smoothing practice. Both the total loan ratio and non-performing loan ratio are significantly in deciding loan loss reserve ratio due to the regulator: China Banking Regulatory Commission (CBRC)’s provisioning policy. The GDP growth rate is positively related with the loan loss reserve ratio and implies that the Chinese banking system is not pro-cyclical and banks’ provisioning behaviour is a forward looking risk assessment over the business cycle. The lagged dependent variable is significant; indicating that on average Chinese banks will adjust their loan loss reserve ratio based on the level in the previous year. In addition, the Chinese banks samples do not support the capital management hypothesis and are not affected by bank size. In terms of the dummy variables, consolidated banking group has higher loan loss reserve ratio than non-consolidated banking group on average. There is no evidence indicating differences are existing in loan loss provisioning behavior among different types of banks in China.